Developing an iPad app for assessment in dance movement therapy. (November 2016) - Dunphy, Kim; Mullane, Sue; Allen, Laura
Highlights: Challenges identified in assessment practice for dance movement therapy. Development of a Framework for Assessment for dance movement therapy for clients with a disability. Two pilot trials indicate positive responses to an i-Pad app for DMT assessment. App use increased professionals' capacity to assess efficiently and efficiently. Abstract: Dance movement therapists face many challenges in implementing effective assessment practices, particularly a dearth of accessible assessment frameworks and functional tools that enable practitioners to collect data. Technological advances are as yet under-utilised in assessment processes. This article introduces Marking the Moves, an iPad app developed to expedite assessment of outcomes of dance movement therapy programs, and discusses pilot trials of its first applications in practice. This app is based on the Framework for Dance Movement Assessment devised by the authors for dance movement therapy programs for clients with disability, including intellectual disability, that measures progress across domains of physical, cognitive, emotional, personal and interpersonal growth. Findings of preliminary trials with therapists and peer professionals in two countries indicate favourable response to the app and its potential for use by dance movement therapists in different contexts and client groups.